A Comparison of the flexural strength of self-cured and dual-cured alkasite restorative filling material an in vitro study - Arellano, Allen Vince S.; Datingaling, Ma. Patrcia; Ocampo, Paolo Vincent G.; Publico, Gian Carlo E.; Santiago, Dan Aron A.; Alfaro, Arlene Cecilia A.; Medina III, Vicente O. (Manila Department of Community Dentistry, University of the Philippines Manila, 2018)
Introduction: Cention N is a new material developed by Ivoclar Vivadent which is said to have physical properties comparable to dental amalgam, an ion-releasing potential and is tooth-colored. It comes in powder and liquid and sets through self-cure with optional light-curing. The study aimed to determine the difference in the flexural strength of self-cured and dual-cured alkasite material.
Methods: Ten Cention N specimens for each group were prepared by mixing the material and packing it into a metal mold assembly. For the self-cured group, each specimen was left undisturbed until fully set, then was immersed in a water bath for an hour before the specimen was removed from the assembly. For the dual-cured group, each specimen was light-cured, then was immersed in a water bath for 15 minutes before the specimen was removed from the assembly. After a specimen from either group was removed from the assembly, it was placed in a water bath until testing. Flexural strengths were determined using a Universal Testing Machine at a crosshead speed of 0.75mm/minute. The data gathered were recorded using Microsoft Excel.
Results: The data were analyzed using Two-Sample T-test and the level of significance was set at α=0.05. Results show that the mean flexural strength for the self-cure group at 71.78 ± 16.09 MPa, and the dual-cure group at 98.63 ± 9.85 MPa. Two sample T-test reveals a significant difference between the mean flexural strength of self-cured and dual-cured alkasite material, with the dual-cured group having higher values. Conclusions: Based on the results, dual-cured alkasite material have a higher flexural strength than the self-cured alkasite material and the difference is statistically significant.
Conclusions: Based on the results, dual-cured alkasite material have a higher flexural strength than the self-cured alkasite material and the difference is statistically significant.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Flexural strength; Cention N; Alkasite